2001
DOI: 10.1247/csf.26.271
|View full text |Cite
|
Sign up to set email alerts
|

Identification of the Core Protein Carrying the Tn Antigen in Mouse Brain: Specific Expression on Syndecan-3.

Abstract: ABSTRACT. We isolated glycoproteins carrying the Tn antigen, which was expressed spatiotemporally in the developing mouse brain. The Tn antigen was expressed on two molecular species with a molecular weight from 200 to 350 kDa and 110 to 160 kDa, as judged on SDS-PAGE. Although the two glycoproteins showed different susceptibilities to heparitinase I and solubilities in a salt solution, after treatment with V8 protease they showed the same mobility corresponding to a molecular weight of 90 kDa on SDS-PAGE, sug… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
12
1
1

Year Published

2003
2003
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(16 citation statements)
references
References 24 publications
2
12
1
1
Order By: Relevance
“…In addition, cell bodies of neuronal cells in the internal granular layer also exhibited positive reactivity. According to the previous studies (24,44), internal granular layer cells were not likely stained with MLS128, and this was different from our present results using HB-Tn1. In contrast, the pp-GalNAc-T13 null mouse showed a remarkable decrease in HB-Tn1 reactivity both in Purkinje cells and in internal granular layer cells (Fig.…”
Section: Fig 6 Hplc Analysis Of In Vitro O-glycosylation Of Muc5accontrasting
confidence: 99%
See 3 more Smart Citations
“…In addition, cell bodies of neuronal cells in the internal granular layer also exhibited positive reactivity. According to the previous studies (24,44), internal granular layer cells were not likely stained with MLS128, and this was different from our present results using HB-Tn1. In contrast, the pp-GalNAc-T13 null mouse showed a remarkable decrease in HB-Tn1 reactivity both in Purkinje cells and in internal granular layer cells (Fig.…”
Section: Fig 6 Hplc Analysis Of In Vitro O-glycosylation Of Muc5accontrasting
confidence: 99%
“…antibody (24,44). It was reported that the triplet Tn antigen is present in late embryonic brain with an expression peak in the early postnatal brain (postnatal 3-7 days, P3-P7), and immunoreactivity for MLS128 was restricted to the cell bodies of Purkinje cells in the P7 mouse brain (44).…”
Section: Fig 6 Hplc Analysis Of In Vitro O-glycosylation Of Muc5acmentioning
confidence: 99%
See 2 more Smart Citations
“…Tissue slices along the longitudinal axis of incisors were stained with rabbit polyclonal antibodies raised against extracellular portions of mouse syndecan core proteins. The specificity of the antibodies was confirmed in the previous study (17,18).…”
Section: Localization Of Mouse Syndecan Core Proteins In the Lower Insupporting
confidence: 75%